Pengaruh Produk, Lokasi, Harga dan Promosi terhadap Minat Beli Konsumen pada Usaha Pempek Mamad Kota Jambi - Laila Farhat (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
A business will be able to survive, achieve growth, and increase the number of consumers' interest if it has implemented the right marketing strategy. This marketing strategy can be in the form of a marketing mix strategy. Pempek Mamad has implemented a marketing mix in the business units it runs. After conducting interviews with the owner of this business, information was obtained that this business was running smoothly and experiencing quite rapid development. That means this business has high appeal or interest among consumers. This will be linked to the aim of this research, to find out the factors in the marketing mix that influence consumer buying interest. This type of research is qualitative with quantitative analysis. The instrument is a questionnaire with a Likert scale of 1-5. The population and sample for this research are consumers of Pempek Mamad, Jambi City, both directly and online purchasing, totaling 100 respondents taken using purposive sampling. Based on the analysis and hypothesis testing, the results obtained in the form of a t test in the coefficient table show that partially the price variable has a very positive and significant influence with a significance value of 0.000 < 0.05. The results of the F test using the ANOVAb table show Fcount > F table (167.219 > 2.70) a significance value that is smaller than alpha (0.000 < 0.05), so it can be concluded that the correlation coefficient is statistically significant for the product variable (X. 1), location (X.2), price (X.3), and promotion (X.4) together influence consumer buying interest (Y).